Dampak Pengembangan Pariwisata Terhadap Kemiskinan di Provinsi Sumatera Barat - Geby Fanesa Adelia; Zul Azhar (Universitas Negeri Padang, 2023)
This study aims to analyze the impact of tourism development on poverty in West Sumatra Province. This type of research is descriptive and associative, using secondary data. This research method uses path analysis. The variables used are Economic Growth (Y1), Poverty (Y2), Tourism (X1), Government spending on infrastructure (X2). The data used is panel data for 19 regencies/cities for the 2016-2021 period, which were obtained from related institutions and agencies. The results of this study indicate that tourism has no influence on poverty through economic growth as a mediating variable. Government infrastructure spending has a positive and significant impact on poverty in West Sumatra Province. Taken together, there is a significant influence between tourism, government spending on infrastructure, and economic growth, on poverty in West Sumatra Province.